Fatal architectures and death by design: The infrastructures of state-sponsored climate disasters in Angola and Mozambique - Blanes, Ruy Llera (Review of African Political Economy, 2023)
This article addresses how African states respond to climate crisis, arguing that, beyond the agency and impact of climate phenomena such as drought and cyclones, they are active participants in the production of climate disasters and emergencies, mostly through infrastructural processes that affect land and resource use, and subsequently livelihoods. To demonstrate this, it uses the cases of the drought in southwestern Angola and cyclones in northern and central Mozambique, where such climate phenomena have exposed ‘fatal architectures’ that have dramatically raised the toll of climate victims and refugees. Both extractivist, agro-industrial and hydroelectric projects, as well as other, more deferred infrastructural designs (roads, communication networks, etc.) have challenged the traditional agency and resilience of local communities. Such new infrastructural projects also illustrate how certain perceived long-term solutions to address the climate crisis with industrial and energy reconversion towards greener energies can still become fatal architectures in the context of climate emergencies.